Entre pitadas e likes: engajamento do consumidor em comunidades virtuais de culinária - Saad, André Scatigno (2020)
Food and its preparation are constant in human life. The increase in the internet access in Brazil also brings this constant to the virtual environment, providing new consumption phenomena. Popular digital platforms such as YouTube, Instagram and Facebook are frequently accessed by a large number of people interested mainly in the free content available on public channels and profiles. Those digital platforms bring together interested and engaged consumers of culinary content in virtual communities of culinary content. Consumer engagement with virtual culinary communities is the focus of this work, which aims to investigate how this engagement happens. To meet this objective, a qualitative research was carried out, with in-depth interviews with 12 consumers of virtual culinary communities resulting in 183 transcript pages. After analyzing the data, the results provided a set of 8 premises about the concept of engagement and its respective cognitive, emotional and behavioral dimensions. Thus, it is expected to contribute to the literature of consumer engagement in virtual communities and to provide key factors for managers and brands that wish to be part and stand out in this scenario.